Analysis of volatility of and dependence between exchange rate and inflation rate in Lao people's democratic republic using copula-based GARCH approach - Tongvang Xiongtoua (2018)
This paper aims to conduct a study of the volatility and dependence between the exchange rate and inflation rate in Laos. The results of the study show that the ARMA (1, 1) - GARCH (1, 1) models were appropriate for two random variables. The KS and Box-Ljung tests for skewed-t distribution and autocorrelation performed in the study found that the two margins were skewed-t distribution and had no autocorrelation. The modeling of the best-fit copula from the testing process found that the time-varying t copula was the best of all static copulas and time-varying copulas in terms of the AIC and the BIC, which means that it has the highest explanatory power of all the dependence structures. In addition, we can see that the indicator of the correlation (dependence parameter:) between the growth rates of the exchange rate and the inflation rate describes a high correlation in the long term, and also evinces that the dependence between the growth rates of the exchange rate and the inflation rate was positive, meaning that when the US Dollar appreciates, the inflation rate increases as well. Thus, this model as the time-varying t copula can help policy makers become more aware of what is likely to happen in the future. © Springer International Publishing Switzerland 2014.